Studying the Effect of COVID-19 on Liver Enzymes and Lipid Profile in Iraqi Recovering Patients (Baghdad Science Journal, 2023)
The Covid-19 virus disease has been shown to affect numerous organs and systems including the liver. The study aimed to compare lipid profiles and liver enzyme levels in individuals who had recovered from Covid-19 infection. To achieve the study objectives, liver Aspartate Aminotransferase (AST), Alanine Aminotransferase (ALT), Alkaline phosphatase (ALP),  Random Blood Sugar (RBS) and Lipid profile which include cholesterol, High-Density Lipoprotein (HDL), Triglycerides (T.G), Low-Density Lipoprotein (LDL), and Very low-density Lipoprotein (VLDL) were determined.One hundred twenty serum samples were obtained, of which fifty samples were utilized as the control healthy persons (not affected by COVID) and seventy samples came from COVID-19 patients who had recovered. Liver enzymes showed a significant increase in serum AST, ALT, and ALP between the two groups (p-values) of 0.001. The lipid profile demonstrated notable ariations which showed an increase in cholesterol, TG, LDL, and VLDL., as well as a decrease in HDL level in the recovered patients’ group compared to the control (p-values) with a value of 0.001. There were no significant differences in RBS between the recovered patients’ group as compared with the control, (p-value) (0.062). Also, body mass index )BMI( and age showed no significant differences. This study concluded that Covid 19 survivors experienced issues with their lipid profiles and liver enzymes